Tracks from the Past, Transport for the Future : China's Railway Industry 1990-2008 and Its Future Plans and Possibilities - World Bank (World Bank, 2012)
This report describes and explains how, in the period 1990-2008, China's railway sector has contributed and responded to the incredibly challenging transport demands generated by China's economic development, and highlights the plans and possibilities that lie ahead. In 1949, China had only 22,000 km of poorly maintained and war-damaged railway line, less than 1,000 km of which was double-tracked with none being electrified. Since then, the government has transformed the railway sector into a vital element of China's national transport system and a key contributor to China's extraordinary record of economic growth. Today, China Rail is the second biggest carrier of rail freight and the biggest carrier of passenger transport in the world. It has the largest combined rail traffic task of any national railway system in the world, carrying about a quarter of the world's railway traffic on about seven percent of the global route-km of public railway. This paper describes how the Ministry of Railways, and its constituent regional railway administrations and other entities, have created a modern rail system by adopting proven international practices and technologies, giving them distinct Chinese characteristics, and adapting them to Chinese circumstances.